POTENTIAL CORRUPTION IN THE VALIDATION POLICIES ON ACQUISITION TAX OF LAND AND OR BUILDING - Lilik Warsito (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The Unitary Republic of Indonesia is a constitutional state based on Pancasila and the Constitution of the Republic of Indonesia in 1945 which aims to realize the livelihood of a nation that is safe, orderly, prosperous, and equitable. In the development of law in Indonesia underwent major changes, fast, and complex. The shift of power centralized to decentralized cause behavioral changes bureaucracy policies both at the central and regional changes from the old paradigm to the new paradigm, sometimes causing the rule of law drowned because of power, which can lead to policies that do not favor of the people. Each power always contains the potential for misuse or arbitrarily implemented, or implemented by exceeding authority. This can happen because of the power contains rights and authority, and the right and authority that makes a higher position.